Divide In Marketing Between Academics And Practitioners - Fernanda Capanema Repsold; Marcus Wilcox Hemais (BBR: Brazilian Business Review)
In marketing, there is a clear divide between academics and practitioners. However, there are few empirical studies in Brazil that help clarify the phenomenon. In light of this context, the present research seeks to understand how academics and practitioners perceive the divide between the academy and businesses and how this affects the applicability of theories, concepts and models in marketing. For this purpose, in-depth interviews were conducted with ten academics who teach marketing and 15 practitioners involved in the area. The reasons for the divide are presented, with emphasis on how the teaching of marketing contributes to the phenomenon. The paper shows how the divide affects the applicability of the discipline, and it gives suggestions on how to reduce the divide. Academics and practitioners show interest in reducing the divide. The difficulties for this to are owing to the different understandings of what marketing is. Such an inconsistency can be explained based on the purposes/reasons that lead these professionals to practice the discipline.